1986
DOI: 10.1172/jci112550
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of adenosine receptor-mediated inhibition of lipolysis. The mechanism involves the development of enhanced cyclic adenosine monophosphate accumulation in tolerant adipocytes.

Abstract: Adipocytes contain adenosine receptors, termed Al receptors, which inhibit lipolysis by decreasing adenylate cyclase activity. The inhibition of lipolysis by adenosine agonists in vivo acutely suppresses the plasma concentrations of free fatty acids (FFA) and triglycerides. We have found that infusions of the adenosine receptor agonist phenylisopropyladenosine (PIA) initially decreases plasma FFA concentrations; however, with prolonged exposure (6 d), rats become very tolerant to the effects of the drug. Adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Previous results suggested that adenosine-receptor agonists (such as PIA) effectively reduce the levels of both plasma triglycerides and unesterified fatty acids when infused into rats (63). Our results emphasize that 3T3-L1 adipocytes with a down-regulated PEMT gene exhibit considerably increased basal lipolysis, and fat pads from Pemt Ϫ/Ϫ mice show a moderate increase in basal lipolysis in comparison with those of WT animals.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous results suggested that adenosine-receptor agonists (such as PIA) effectively reduce the levels of both plasma triglycerides and unesterified fatty acids when infused into rats (63). Our results emphasize that 3T3-L1 adipocytes with a down-regulated PEMT gene exhibit considerably increased basal lipolysis, and fat pads from Pemt Ϫ/Ϫ mice show a moderate increase in basal lipolysis in comparison with those of WT animals.…”
Section: Discussionsupporting
confidence: 68%
“…Adipocytes express adenosine A1 receptors (62) that effectively suppress adenylate cyclase, thereby inhibiting catecholamine-mediated triglyceride hydrolysis (63). Previous results suggested that adenosine-receptor agonists (such as PIA) effectively reduce the levels of both plasma triglycerides and unesterified fatty acids when infused into rats (63).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is possible to achieve a greater functional selectivity using partial agonists than full agonists; e.g., CVT-3619 does not significantly affect heart rate and blood pressure at doses that have significant antilipolytic activity (8). Furthermore, partial agonists of G protein-coupled receptors have been suggested to cause less pronounced receptor desensitization (19,37) than full agonists with prolonged and continuous exposure (16,23). In that context, we have shown that the antilipolytic effects (the magnitude and the duration the FFA-lowering effect) of CVT-3619 are well-maintained over three consecutive acute administrations (8); however, it remains to be determined whether the antilipolytic effect of CVT-3619 is sustained over long-term use.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude and the duration of the FFA-lowering effect of CVT-3619 were similar for all three injections, suggesting that the effect of this agonist does not undergo tachyphylaxis. Desensitization of the antilipolytic effect of A 1 receptors has been shown to occur with prolonged and continuous exposure to high concentrations of an A 1 agonist, R-PIA (Hoffman et al, 1986a). R-PIA is a full agonist and thus more likely to cause desensitization.…”
Section: Discussionmentioning
confidence: 99%